MURABAHAH (Pengertian dan Pembiayaan Murabahah Menurut Fatwa Dewan Syariah Nasional) - Setya Surya Wardhana; Farikhatul Lailiyah, Hidayatus Syarifah, Moh. Syaiful Rahman (CV. Adiba Aisha Amira, 2024)
Muamalah is the basis and part of the overall teachings of Islam. Muamalah, worship, and morals have a relationship with each other, the three components are very important if we want to practice the teachings of Islam as a whole and not halfway. If the three components have not been carried out, it means that they have not carried out the teachings of Islam perfectly as recommended by the Qur'an and Hadith. According to Bank Muamalat, murabahah is a sale and purchase process between the bank and the customer, where the bank will provide goods by buying goods according to the buyer's criteria, then the bank will sell to the buyer with a high bid that makes a source of profit for the bank. The murabahah agreement is the basis on which goods are traded in installments and increases the bank's profit margin. Murabahah can be implemented in two ways, purchasing with orders and without orders. Islamic banks are Islamic banking institutions that have an intermediary function, namely Islamic banks collect public money in the form of deposits and channel it through the financial system. One way to channel money to Islamic banks is through murabahah financial products.